The Price Sensitivity of Health Plan Choice among Retirees: Evidence from the German Social Health Insurance - Amelie Wuppermann; Sebastian Bauhoff; Markus Grabka (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
We investigate two determinants of the price sensitivity of health plan demand among retirees in the German social health insurance (SHI): the size of the choice set and the salience of premium differences. We use variation in the choice set over time and between regions, and an increase in the salience of premium differences introduced by a recent reform that changed how premiums are framed. Using information on health plan switches in the German Socio Economic Panel, augmented with information on individuals choice sets we find that retirees are less likely to react to potential savings from switching when they have more plans to choose from and when differences between premiums are less salient. The results imply that simplifying choices could save retirees money and also improve the functioning of the health insurance market.
Keywords: I11; D12; C23; 330